2018
DOI: 10.1155/2018/1390483
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress in Cardiomyocytes during the Aging Process in Rats Treated with Resveratrol

Abstract: The substantial increase in the number of elderly people in our societies represents a challenge for biology and medicine. The societies of the industrialized countries are subject to a progressive aging process that translates into an increase in the cardiovascular risk of the population. In the present work, the activity of catalase and superoxide dismutase was evaluated, as well as markers of oxidative stress (concentration of nitric oxide and total lipoperoxidation in its main components: malondialdehyde a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…The rat model of cerebral hemorrhage was established using the modified ischemia/reperfusion method as previously described (10). Rats received right middle cerebral artery occlusion for 90 min and reperfusion by withdrawal of the filament at 37°C Immediately, rats with ischemia/reperfusion-induced cerebrovascular injury were randomly divided into two groups (each, n=8) and were administered an intravenous injection of resveratrol (10 mg/kg/day; Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) or the same volume of PBS (serving as the control) as described previously (11). The treatments were continued for 20 days.…”
Section: Methodsmentioning
confidence: 99%
“…The rat model of cerebral hemorrhage was established using the modified ischemia/reperfusion method as previously described (10). Rats received right middle cerebral artery occlusion for 90 min and reperfusion by withdrawal of the filament at 37°C Immediately, rats with ischemia/reperfusion-induced cerebrovascular injury were randomly divided into two groups (each, n=8) and were administered an intravenous injection of resveratrol (10 mg/kg/day; Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) or the same volume of PBS (serving as the control) as described previously (11). The treatments were continued for 20 days.…”
Section: Methodsmentioning
confidence: 99%
“…An antioxidant-rich diet is therefore beneficial for preventing the effects of ROS in the cardiovascular system [ 39 ]. Studies by Aguilar-Alonso et al on oxidative stress markers (total lipoperoxidation and nitric oxide (NO) levels) as well as catalase activity and superoxide dismutase (SOD) in aging rat cardiomyocytes treated with resveratrol showed a decrease in NO Levels and total lipoperoxidation, but the activity of catalase and SOD was not significantly affected, and it was concluded that the anti-aging and cardioprotective properties of resveratrol are mediated mainly by its antioxidant effects [ 40 ].…”
Section: Reviewmentioning
confidence: 99%
“…The combination of Res and exercise has been found beneficial on vascular function reducing inflammatory markers and enhancing vessel responsiveness [ 66 ]. However, a recent work reported that the beneficial effect of resveratrol could be due to an antioxidant effect without any evidence of Sirt1 activation [ 67 ].…”
Section: Exercise and Sirtuins In Cardiovascular Diseasesmentioning
confidence: 99%